A proposed framework for mobile Internet QoS customer satisfaction using big data analytics techniques - Yusuf-Asaju, Ayisat W.; Md Dahalin, Zulkhairi; Ta'a, Azman (2016)
In the past few years, the Nigeria telecommunication industry has experienced tremendous growth and changes to the extent that customers find it much easier to access the internet through their mobile phones.However, the growth in mobile telecoms subscribers comes with challenges of quality of service, which lead to fluctuations in customer satisfaction.Therefore, the present study proposed a customer satisfaction prediction model through the Key performance indicators obtained from the objective measurement of the network traffic using extended and exhaustive study of the literature.The proposed framework would guide mobile network operators on strategies to embark on in order to retain their customers within the network.